Mussolini's Children : Race and Elementary Education in Fascist Italy - McLean, Eden K. (Book collections on Project MUSE., 2018)
""Mussolini's Children" uses modern theories of race and biopolitics and the lens of state-mandated youth culture--elementary education and the auxiliary organizations designed to mold the minds and bodies of Italy's children between the ages of five and eleven--to understand the evolution of Fascist racism"--